Math, asked by snehasneha4136, 6 months ago

if x-1/x=3 then find the value of x^3-1/x^3​

Answers

Answered by EliteSoul
94

Given :

\sf x - \dfrac{1}{x} = 3

To find :

\sf Value \ of \ \bf{ x^3 - \dfrac{1}{x^3}}

Solution :

\star\sf \ x - \dfrac{1}{x} = 3 \qquad\quad ..(1)

Now using identity :

\bigstar \ \underline{\bold{x^3 - y^3 = (x - y)^3 + 3xy(x - y)}}

Here, x = x and y = 1/x

Now putting values,

\longmapsto\sf x^3 - \dfrac{1}{x^3} = \bigg(x - \dfrac{1}{x} \bigg)^3 + 3 \times x \times \dfrac{1}{x} \bigg(x - \dfrac{1}{x} \bigg) \\\\ \\ \longmapsto\sf x^3 - \dfrac{1}{x^3} = 3^3 + 3 \times 3 \\\\ \\ \longmapsto\sf x^3 - \dfrac{1}{x^3} = 27 + 9 \\\\ \\ \longmapsto\underline{\boxed{\mathfrak{x^3 - \dfrac{1}{x^3} = 36 }}} \ \bigstar

\therefore \underline{\textsf{Required value of expression = {\textbf{36}}}}

Answered by KingSrikar
10

\sf{\displaystyle x-\frac{1}{x}=3}

❥ Take Cube Root on Both Sides of the Equation

  • Cube root means Taking Whole Power 3 to Both Sides

\to\sf{\displaystyle \left(x-\frac{1}{x}\right)^3=3^3}

❥ Apply Algebraic Identity : \sf{(a -b)^3 = a^3 -b^3-3ab(a-b)}

  • We have \sf{a=x} and \sf{b=1/x} , Now Substitute the Values

\to\sf{\displaystyle x^3-\left(\frac{1}{x}\right)^3-3\cdot \:x\cdot \frac{1}{x}\left(x-\frac{1}{x}\right)=27}

❥ Cancel \sf{x} and \sf{1/x}

\to\sf{\displaystyle x^3-\left(\frac{1}{x}\right)^3-3\left(x-\frac{1}{x}\right)=27}

❥ We are already given that \sf{x-(1/x)=3}

\to\sf{\displaystyle x^3-\left(\frac{1}{x}\right)^3-3\left(3\right)=27}

\to\sf{\displaystyle x^3-\left(\frac{1}{x}\right)^3-9=27}

❥ Add 9 to Both Sides of the Equation

\to\sf{\displaystyle x^3-\left(\frac{1}{x}\right)^3-9+9=27+9}

\bigstar\:\:\underline{\boxed{\to\sf{\displaystyle x^3-\left(\frac{1}{x}\right)^3=\textsf{\textbf{36}}}}}\:\:\bigstar

Similar questions